Labranza mecanizada y su influencia en la productividad del cultivo de sorgo (Sorghum bicolor L Moench.)” - Miguez Guamán, Emilio Albert (2022)
It is important for sorghum producers to use all combinations of mechanized tillage systems in grain sorghum planting, from traditional to no-till. Among each of the tillage systems there are unique tillage structures and combinations between them, which can be adapted to each location, depending on soil type and climate. Soil preparation, planting and harvesting in sorghum cultivation ensures that the soil is free of clods and weeds to ensure good planting, and so that the newly germinated plants can develop quickly. The first task to be carried out is plowing, which should be as deep as possible to a depth of 15 cm. In order to complement the plowing, a cross plowing is done. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about mechanized tillage and its influence on the productivity of the sorghum crop (Sorghum bicolor L Moench). From the above detailed, it was determined that within sorghum crop production, five basic tillage operations can be highlighted and that each one of them has a selected component of operations that it performs, among them: turning, mixing, raking, spraying and compacting. Soil tillage is critical to plant booming and sorghum crop yields. The advantages of accurate tillage include sufficient aeration for root development, adequate water movement in the soil (infiltration, percolation, and drainage), sufficient soil temperature law for root development and plant booming, and adequate moisture retention for plant use. There are different tillage systems used in grain sorghum planting, from traditional to no-tillage, among them we have the following: conventional tillage, reduced tillage and zero tillage or conservation tillage.